Ferrates(FeVI, FeV, and FeIV) oxidation of iodide: Formation of triiodide - Kralchevska, Radina P; Sharma, Virender K; Machala, Libor; Zboril, Radek (Chemosphere, 2016)
The presence of iodide (I(-)) in water during disinfection and oxidative treatment of water is a potential health concern because of the formation of iodinated disinfection by-products (DBPs), which may be more toxic than chlorinated DBPs. The kinetics of the oxidation of I(-) by a greener oxidant, ferrate(VI) (Fe(VI)O4(2-), Fe(VI)) was determined as a function of pH. The second-order rate constants (k, M(-1) s(-1)) decreased from 3.9 × 10(4) M(-1) s(-1) at pH 5.0 to 1.2 × 10(1) M(-1) s(-1) at pH 10.3. The kinetics results could be described by the reactivity of monoprotonated species of Fe(VI) (HFe(VI)O4(-)) with I(-). In excess I(-) concentration, triiodide (I3(-)) was formed and the stoichiometry of ∼1:1 ([Fe(VI)]:[I3(-)]) was found in both acidic and basic pH. Ferrate(V) (Fe(V)O4(3-), Fe(V)) and ferrate(IV) (Fe(VI)O4(4-), Fe(IV)) also showed the formation of I3(-) in presence of excess I(-). A mechanism of the formation of I3(-) is proposed, which is consistent with the observed stoichiometry of 1:1. The oxidative treatment of I(-) in water will be rapid (t1/2 = 0.6 s at pH 7.0 using 10 mg L(-1) K2FeO4). The implications of the results and their comparison with the oxidation of I(-) by conventional disinfectants/oxidants in water treatment are briefly discussed.
Keywords: železo; Water Pollutants, Chemical; Oxidants; čištění vody; Oxidation-Reduction; jodidy; oxidace-redukce; Kinetics; Water Purification; Iron; dezinficiencia; oxidancia; Halogenation; Disinfectants; Iodides; halogenace; kinetika; chemické látky znečišťující vodu